Optimalisasi Pendekatan Culturally Responsive Teaching (CRT) dalam Pembelajaran Abad 21 - Priya Kusuma Bahari; Radeni Sukma Indra Dewi; Ratna Ekawati (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
21st-century learning demands innovation and creativity in teaching practices. In its implementation, educators need the skill to choose approaches that align with the characteristics of 21st-century students. Learning approaches can be used as a strategy to create an effective and inclusive learning environment. This research examines the optimization of the Culturally Responsive Teaching (CRT) approach in the context of 21st-century learning, with a focus on the importance of recognizing the cultural diversity of students. The condition of Indonesia's diversity presents both challenges and opportunities in the educational process. The diverse conditions of students present a challenge for educators in achieving equality in learning facilities. Thus, with the implementation of the CRT approach, it is expected to enhance student engagement, learning outcomes, and the creation of an inclusive learning climate. This research uses the Systematic Literature Review (SLR) method, by searching and analyzing related literature from various academic sources over the past five years. Data analysis was conducted by reviewing several identified journals, followed by generalization for deeper analysis. The research results show that the application of the CRT approach not only creates an inclusive learning environment but also encourages the development of students' social and academic skills. These findings underscore the need to adapt teaching methods to meet the diverse needs of students, as well as provide practical recommendations for educators to implement them effectively.